Parade - Cusk, Rachel, 1967- (Farrar, Straus and Giroux, 2024)
"Midway through his life, the artist G begins to paint upside down. Eventually, he paints his wife upside down. He also makes her ugly. The paintings are a great success. In Paris, a woman is attacked by a stranger in the street. Her attacker flees, but not before turning around to contemplate her victim, like an artist stepping back from a canvas. At the age of twenty-two, the painter G leaves home for a new life in another country, far from the disapproval of her parents. Her paintings attract the disapproval of the man she later marries. When a mother dies, her children confront her legacy: the stories she told, the roles she assigned to them, the ways she withheld her love. Her death is a kind of freedom."--